Monetary policy rules and the inequality-augmented Phillips curve - Lilian Rolim; Laura Carvalho; Dany Lang (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2023)
We explore the relationship between inequality, unemployment, and inflation by considering the evidence that low-wage workers are more exposed to business cycle fluctuations. The analysis is undertaken in an extended version of the stock-and-flow consistent agent-based model by Rolim et al. (2023), in which inflation and inequality result from the social conflict over income distribution. The inflation-unemployment-inequality nexus leads to the inequality-augmented Phillips curve relating higher levels of unemployment to lower inflation rates and more inequality. We then perform two sets of experiments to investigate the implications of this nexus further. The first experiment shows that the decrease in low-wage workers' bargaining power could explain the flattening of the Phillips curve and the increase in income and wage inequalities. The second experiment contrasts different monetary policy rules and compares the implications for inequality dynamics. In line with the inequality-augmented Phillips curve, the rules have important implications for wage and income inequalities: a monetary policy rule that prioritizes low inflation rates is associated with higher unemployment and higher inequality levels.
Keywords: C63; D3; E2; E3; E4; 330; Phillips curve; inflation; unemployment; inequality; monetary policy; bargaining power